Farmers' Perceived Transaction Costs in Relation to Slaughterhouses of Different Ownership Structure. Issue 1 (20th December 2012) - Hess, Sebastian; Lind, Lena W.; Liang, Se
ABSTRACT The raison‐d'être of traditional cooperatives is claimed to be their capacity to reduce farmers' transaction costs. Hence, one would expect transaction costs to increase when a traditional cooperative is transformed into a hybrid cooperative. The present study investigates this hypothesis. The empirical data originates from a survey with suppliers of Swedish Meats, a cooperative that used to dominate the Swedish meat sector. However, it lost the cooperative elements as external investors got a share of the ownership in 2007. Results indicate that the importance of typical drivers of perceived transaction costs are not homogeneously distributed. A subgroup of respondents still considers the former cooperative as a safe and trustworthy partner with reliable market information. Successful, entrepreneurial farmers instead perceive higher transaction costs when dealing with the hybrid cooperative. Geographical location and neighboring networks are insignificant. In general, the results confirm that the hybrid cooperative has lost its role as a cooperative.